Application of Flower-shaped Japanese Smock Technique on Evening Party Dresses - Raihanah Zahidah; Mila Karmila (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2025)
Fashion design has undergone significant development, particularly in creating new innovations in the form of clothing that combines aesthetic elements from fabric manipulation techniques. One fabric manipulation technique that has regained popularity is smocking. The aim of this research is to produce clothing with a distinctive look by applying Japanese smocking techniques in the form of flowers to evening wear designs in order to create exclusive products. To achieve this objective, this study employs the Practice-led Research method, which emphasizes the following stages: exploration, realization, design, and presentation. The focal point is the floral motif created using the smock technique on satin fabric, complemented by tulle glitter accents on the peplum, resulting in an exclusive evening gown. The research results show the creation of an off-shoulder garment design with asymmetrical peplum details and an H-shaped silhouette that emphasizes a glamorous impression, complemented by Japanese smocking techniques in the shape of flowers on the shoulders with additional pearl accents, as well as the use of sateen canalli and glitter tulle materials that reinforce the luxurious impression. Expert evaluations indicate that this technique offers aesthetic and innovative value, though further development is recommended in terms of application variations and materials. This research contributes to the development of fabric manipulation designs that are not only aesthetically pleasing but also functionally and commercially relevant in the fashion industry, particularly for evening gown categories.